2004
DOI: 10.5650/jos.53.17
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Effective Dose of Plant Sterol on Serum Cholesterol Concentration in Japanese Subjects and Safety Evaluation of Plant Sterol Supplemented in Mayonnaise

Abstract: For examination of the title parameters, study was made in which forty healthy male subjects (serum cholesterol concentration 170 309 mg/dL) were fed 0, 200, 400, 600, or 800 mg/day of free plant sterol supplemented in mayonnaise for 4 consecutive weeks. Only the 800 mg/day group significantly reduced serum cholesterol by the paired t-test (Exp.1). Thirtytwo healthy males (serum cholesterol, 184 285 mg/dL) were made to consume plant sterol as ester at 0, 800, 1600, or 2400 mg/day. In all cases at more than 800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been reported that the minimal effective dose of plant sterols that lowers serum cholesterol concentrations is more than 800 mg/day 2) , which was confirmed in a double-blind, placebo-controlled study in mildly hypercholesterolemic Japanese subjects 3,4) . Because only negligible amounts of plant sterols are absorbed by the small intestine, plant sterols are considered safe in foods for reducing serum cholesterol concentrations 1) .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has been reported that the minimal effective dose of plant sterols that lowers serum cholesterol concentrations is more than 800 mg/day 2) , which was confirmed in a double-blind, placebo-controlled study in mildly hypercholesterolemic Japanese subjects 3,4) . Because only negligible amounts of plant sterols are absorbed by the small intestine, plant sterols are considered safe in foods for reducing serum cholesterol concentrations 1) .…”
Section: Introductionmentioning
confidence: 80%
“…Plant sterols consist of two types: free plant sterols and plant sterol esters. It has been reported that both free plant sterols and plant sterol esters reduce serum cholesterol concentrations 2) . Free plant sterols do not readily dissolve in oil and water; therefore, they are not supplemented in processed foods.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that some responders are prone to increased serum cholesterol concentrations when cholesterol is ingested [ 42 , 43 ]. Furthermore, dietary influences such as functional components that reduce cholesterol absorption, such as phytosterols, soy protein, or dietary fiber, should be considered [ 44 , 45 , 46 , 47 , 48 ]. Chicken eggs’ functional components, specifically egg yolk phospholipids, have been reported to suppress cholesterol absorption [ 49 ].…”
Section: Egg White Protein Improves Lipid Metabolismmentioning
confidence: 99%